Advances in image-guided intratumoral drug delivery techniques - Solorio, Luis (Ther Deliv, 2010)
Image-guided drug delivery provides a means for treating a variety of diseases with minimal systemic involvement while concurrently monitoring treatment efficacy. These therapies are particularly useful to the field of interventional oncology, where elevation of tumor drug levels, reduction of systemic side effects and post-therapy assessment are essential. This review highlights three such image-guided procedures: transarterial chemoembolization, drug-eluting implants and convection-enhanced delivery. Advancements in medical imaging technology have resulted in a growing number of new applications, including image-guided drug delivery. This minimally invasive approach provides a comprehensive answer to many challenges with local drug delivery. Future evolution of imaging devices, image-acquisition techniques and multifunctional delivery agents will lead to a paradigm shift in patient care.